Exploring the synergy of technical and social sciences: an overview of professor Joanicjusz Nazarko’s 45-year scientific journey - Wilczewska, Martyna; Bokun, Katarzyna; Ginevičius, Romualdas (Journal of Business Economics and Management, 2024)
This article presents Professor Joanicjusz Nazarko’s outstanding achievements in research, scientific cooperation, teaching and organizational work, in celebration of the 45th jubilee of his scientific work. Over the years, Professor Nazarko has contributed significantly to the development of technical and social sciences in Poland. He authored more than 300 publications, which constitutes a substantial knowledge base on its own. Using bibliometric and statistical methods and techniques, we present an overview of Professor’s most important scientific achievements and major works. We also highlight his efforts to establish a national and international network for scientific cooperation. Lastly, we present his didactic successes. This jubilee serves as the opportunity to recognize and honour Professor Joanicjusz Nazarko’s significant contribution to the development of science in Poland.